Endogenous growth and global divergence in a multi-country agent-based model - Giovanni Dosi; Andrea Roventini; Emanuele Russo (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2017)
In this paper we present a multi-country, multi-industry agent-based model investigating the different growth patterns of interdependent economies. Each country features a Schumpeterian engine of endogenous technical change which interacts with Keyneasian/Kaldorian demand generation mechanisms. National growth trajectories are driven by firms' accumulation of technological knowledge, which in turn also leads to emergent specialization patterns in different industries. Interactions among economies occur via trade flows, stemming from the competition of firms in international markets. Simulation results show the emergence of persistent income divergence among countries leading to polarization and club formation. Moreover, each country experiences a structural transformation of its productive structure during the development process. Such dynamics results from firm-level virtuous (or vicious) cycles between knowledge accumulation, trade performances, and growth dynamics. The model accounts for a rich ensemble of empirical regularities at macro, meso and micro levels of aggregation.
Keywords: F41; F43; O4; O3; 330; Endogenous growth; structural change; technology-gaps; global divergence; absolute; advantages; agent-based models